Perceptions and Attitudes toward COVID-19 Vaccination among Pregnant and Postpartum Individuals - Siegel, Molly R.; Lumbreras-Marquez, Mario I.; James, Kaitlyn; McBay, Brandon R.; Gray, Kathryn J.; Schantz-Dunn, Julianna; Diouf, Khady; Goldfarb, Ilona T. (American Journal of Perinatology, 2022)
Objective This study aimed to characterize attitudes toward novel coronavirus disease 2019 (COVID-19) vaccination and to evaluate factors associated with vaccine uptake among pregnant individuals.Study Design An anonymous survey was distributed to a convenience sample of pregnant individuals receiving prenatal care at two large urban academic hospitals in a single health care network in Massachusetts. Individual demographic variables were included in the survey along with questions assessing attitudes toward COVID-19 and vaccination in pregnancy. Data were analyzed using parametric or nonparametric tests when appropriate, and associated odds ratios (OR) were calculated via univariable logistic regression.Results There were 684 surveys distributed, and 477 pregnant and postpartum individuals completed the survey, for a response rate of 69.7%. Overall, 233 (49.3%) had received or were scheduled to receive a COVID-19 vaccine. Age, White race, non-Hispanic or Latinx ethnicity, working from home, and typical receipt of the influenza vaccine were associated with COVID-19 vaccination. Further, 276 respondents (58.4%) reported that their provider recommended the COVID-19 vaccine in pregnancy; these participants were more likely to have received a vaccine (OR = 5.82, 95% confidence interval [CI]: 3.68–9.26, p < 0.005). Vaccinated individuals were less likely to be worried about the effects of the vaccine on themselves (OR = 0.18, 95% CI: 0.12–0.27, p < 0.005) or their developing babies (OR = 0.17, 95% CI: 0.11–0.26, p < 0.005). Unvaccinated individuals were less likely to report that it is easy to schedule a COVID-19 vaccine (OR = 0.56, 95% CI: 0.34–0.93, p = 0.02), to travel to receive a vaccine (OR = 0.19, 95% CI: 0.10–0.36, p < 0.005), and to miss work to receive a vaccine (OR = 0.30, 95% CI: 0.18–0.48, p < 0.005).Conclusion Strategies are needed to improve patient education regarding vaccine side effects and safety in pregnancy. Policy changes should focus on making it feasible for patients to schedule a vaccine and miss work without loss of pay to get vaccinated.Key Points
Keywords: pregnancy; vaccine hesitancy; racial disparities; COVID-19; vaccine barriers